Oral Health Awareness Among Parents of Differently Abled Children : A study in North Indian Population - Poonam Agrawal; Kanak Priya; Dinesh Kumar Bagga (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction Good oral health is of paramount importance not only for chewing but also plays a major rolein overall healthy development of a child. Differently abled children may not be able to look after their oralhealth and hygiene themselves. Every child has the equal right for healthy development and opportunities invarious fields of life. As most of the differently-abled children perform their regular activities with the helpof or under the supervision of a family member or caregiver, it is important for the parents or caregivers tohave sufficient knowledge about oral hygiene measures in order to guide the child efficiently.Materials and Method: A structured modified oral health awareness questionnaire having two componentssociodemographic data and questionnaire- related to oral hygiene habits, sugar exposure, and oral healthseeking behaviour was constructed. The parents and guardians of 200 institutionalized physically/mentallychallenged students were asked to fill up the questionnaires and were then educated regarding proper oralhygiene measures with the help of posters and audio-visual aids.Conclusion: Differently children, due to limited ability and inadequate guidance on oral hygiene maintenance,are prone to poor oral health. There is lack of knowledge of importance of oral health in parents of differentlyabled children. It is the duty of oral health care workers to educate the parents of differently abled childrenabout significance of oral health and how they can train their child for maintenance of proper oral health andhygiene for their overall healthy development.